2018
DOI: 10.1126/sciadv.1701645
|View full text |Cite
|
Sign up to set email alerts
|

Nature, formation, and distribution of carbonates on Ceres

Abstract: Hydrated carbonates indicate that the surface of Ceres is recent and dehydration is ongoing, implying a still-evolving body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 34 publications
(76 reference statements)
4
92
0
Order By: Relevance
“…No similar faculae are observed on any other mountains independent of rim/wall faculae in impact craters. Mons contain some Na carbonate associated with bright material Carrozzo et al, 2017 ). The rim/wall faculae are compositionally similar to many floor faculae, but the dominant carbonate tends to be Mg-Ca carbonate whereas floor faculae and the most extensive rim/wall faculae (e.g.…”
Section: Ahuna Monsmentioning
confidence: 99%
“…No similar faculae are observed on any other mountains independent of rim/wall faculae in impact craters. Mons contain some Na carbonate associated with bright material Carrozzo et al, 2017 ). The rim/wall faculae are compositionally similar to many floor faculae, but the dominant carbonate tends to be Mg-Ca carbonate whereas floor faculae and the most extensive rim/wall faculae (e.g.…”
Section: Ahuna Monsmentioning
confidence: 99%
“…Previous studies (e.g. Carrozzo et al, 2018) showed that occurrence of carbonate content increases the reflectance while the opaque causes darkening. Albedo was calculated by applying a Hapke photometric correction to the entire dataset as described by Ciarniello et al, 2017.…”
Section: Albedo Maps At 12 μMmentioning
confidence: 91%
“…Unlike the two bands described in the previous section, the absorption at 4 µm shows a band center variability. It moves toward longer wavelengths indicating a compositional variation (Carrozzo et al, 2018). Generally, the 4 µm bands is centered at 3.95 µm, showing the presence of Mgcarbonates, even if in specific regions, it shifts to 3.99 µm, suggesting the presence of Na-carbonates (De Sanctis et al, 2016, Carrozzo et al 2018, Fig.…”
Section: Vir Band Center and Depth At 4 μMmentioning
confidence: 92%
See 2 more Smart Citations